Decentralized infrastructure development in the Philippines: Constraints, governance, and regulation in water - Dante B. Canlas; Margarita Debuque-Gonzales (University of the Philippines, School of Economics (UPSE), 2020)
This chapter discusses infrastructure development in the Philippines under decentralization using illustrations mainly in the water sector. It opens up a study of the constraints and challenges in governance and regulation that local government units (LGUs) face in narrowing down the infrastructure gaps in their various jurisdictions. To enable LGUs' project proposals to get into the priority public investment program of the national government, the former must have skilled human resources capable of conducting the technical, legal, and financial analysis required. In governance, they must be able to navigate the complexities of water-pricing regulation. At the start, LGUs will need a good deal of technical, legal, and financial assistance from the national government in raising their capacity to overcome the challenges. However, through learning-by doing and as LGUs are able to mobilize additional resources using their power to impose tax and non-tax measures, decentralized infrastructure development can take off, guided by an effective division of labor between the national government and LGUs.
Keywords: H7; O5; 330; decentralization; infrastructure development; governance and regulation; Philippines